Carbon exchange between ecosystems and atmosphere in the Czech Republic is affected by climate factors - Marek, Michal V; Janouš, Dalibor; Taufarová, Klára; Havránková, Kateřina; Pavelka, Marian; Kaplan, Věroslav; Marková, Irena (Environmental pollution (Barking, Essex, 2011)
By comparing five ecosystem types in the Czech Republic over several years, we recorded the highest carbon sequestration potential in an evergreen Norway spruce forest (100%) and an agroecosystem (65%), followed by European beech forest (25%) and a wetland ecosystem (20%). Because of a massive ecosystem respiration, the final carbon gain of the grassland was negative. Climate was shown to be an important factor of carbon uptake by ecosystems: by varying the growing season length (a 22-d longer season in 2005 than in 2007 increased carbon sink by 13%) or by the effect of short- term synoptic situations (e.g. summer hot and dry days reduced net carbon storage by 58% relative to hot and wet days). Carbon uptake is strongly affected by the ontogeny and a production strategy which is demonstrated by the comparison of seasonal course of carbon uptake between coniferous (Norway spruce) and deciduous (European beech) stands.
Keywords: podnebí; buk (rod); zemědělství; smrk; Fagus; ekosystém; Picea; Poaceae; stromy; Trees; Ecosystem; Czech Republic; lipnicovité; Agriculture; Carbon Sequestration; sekvestrace uhlíku; Climate; Česká republika